Development of a high-strength electric conductive epoxy binder with glass functions temperature above 200°C - Kiselkov, D.M.; Slobodinyuk, A.I. (Perm Federal Research Centre Journal, 2020)
A high-temperature epoxy binder has been developed, modified with various nanoscale fillers in order to increase the structural strength and electrical conductivity of the material. «Taunit -M» series multiwall carbon nanotubes and Tuball single wall carbon nanotubes have been used as fillers. The effect of these fillers on the electrophysical and physico-mechanical properties of the binder has been studied. The morphology of nanofillers has been studied both in epoxy resin and in the cured composite. «Taunit-М» are more prone to agglomeration, which complicates their uniform distribution and are less effective both in providing electrical conductivity and in increasing the strength characteristics.